PENGEMBANGAN KURIKULUM EKSTRAKURIKULER TARI DI TK BINAYOGA PELUTAN BERBASIS MODEL SKILBECK DAN KEMMIS & MC. TAGGART - Rullis Indriyanti; Dhiniaty Gularso (STKIP Subang, 2026)
This study aims to describe the curriculum development of dance extracurricular activities at TK Binayoga Pelutan based on the Skilbeck curriculum development model and the Kemmis & Mc. Taggart action research model. The program was designed to develop children's physical, cognitive, social-emotional, artistic, and cultural competencies through Dolalak, Rampak, and Meong dances. This study employed a qualitative best practice approach conducted at TK Binayoga Pelutan, Purworejo Regency. Data were obtained through observation, documentation, interviews, and curriculum analysis. The results indicate that the curriculum was developed through situation analysis, objective formulation, program planning, implementation, reflection, and continuous evaluation. The curriculum implementation integrated humanistic, technological, and social reconstruction approaches. The findings revealed positive impacts on children's motor development, self-confidence, creativity, cooperation skills, and appreciation of local culture. In addition, the program strengthened collaboration among schools, parents, cultural practitioners, and the community. Therefore, dance extracurricular activities can serve as an innovative curriculum development model that supports holistic child development while preserving local cultural heritage.